PENGARUH PELAKSANAAN PROGRAM HAFALAN JUZ 30 TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AL-QUR’AN HADIS DI MTS NEGERI 1 KOTA MAKASSAR - Rusmin B, Muhammad; Qamar, Syamsul; Mosiba, Risna (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to describe the implementation of the juz 30 memorization program at MTs Negeri 1 Makassar City, describe the learning outcomes of students in the Qur'an hadith subject, and analyze the effect of implementing the juz 30 memorization program on student learning outcomes in al- Qur'an hadith at MTs Negeri 1 Makassar City. This research is a quantitative research with ex post facto method. The results showed that: 1) the implementation of the juz 30 memorization program, there were 2 people who were in the high category with a percentage of 7.5%, 37 people who were in the medium category with a percentage of 90%, and 1 person who was in the low category with a percentage of 2.5 %. 2) the learning outcomes of students in the Qur'an hadith subject, there are 2 people who are in the high category with a percentage of 7.5%, 32 people are in the medium category with a percentage of 77.5% and 6 people are in the low category with percentage of 15%. 3) the effect of the implementation of the juz 30 memorization program on student learning outcomes in the Qur'an hadith subject at MTs Negeri 1 Makassar City obtained Tcount > Ttable data, namely 5.027 > 2.028 and sig. 0.003 <0.05 then HI is accepted. So it can be concluded that the implementation of the juz 30 memorization program has an effect on student learning outcomes in the Qur'an hadith subject at MTs Negeri 1 Makassar City. The implications of this study are: 1) the juz 30 memorization program is an important factor in student learning outcomes. 2) in an effort to improve learning outcomes, make habits starting from yourself, 3) school principals and teachers always improve their performance so that even during a pandemic, students can still maximize their learning and not reduce their intellectual quality and learning outcomes.